Lysosomal Cathepsin A Plays a Significant Role in the Processing of Endogenous Bioactive Peptides - Timur, Zehra Kevser; Akyildiz Demir, Secil; Seyrantepe, Volkan (Frontiers in Molecular Biosciences, 2016)
Lysosomal serine carboxypeptidase Cathepsin A (CTSA) is a multifunctional enzyme with distinct protective and catalytic function. CTSA that is present in the lysosomal multienzyme complex facilitates correct lysosomal routing, stability and activation of betagalactosidase and alpha-neuraminidase. In addition, CTSA plays a role in the inactivation of bioactive peptides including bradykinin, substances P, oxytocin, angiotensin I and endothelin-I by cleavage of one or two amino acid(s) from the C-terminal ends. In this study, we aimed to elucidate the regulatory role of CTSA on bioactive peptides in a knock-in mouse model of CTSAS190A. We evaluated the levels of bradykinin, substances P, oxytocin, angiotensin I and endothelin-I in the kidney, liver, lung, brain and serum of the CTSAS190A mouse model at three- and six-months of age. Our results suggest that CTSA selectively contributes to the processing of bioactive peptides in different tissues of CTSAS190A mice compared to those of age-matched wild-type mice.